UPAYA MENINGKATKAN KEMAMPUAN PARENTING KAUM IBU DENGAN METODE BIMBINGAN KELOMPOK (Penelitian Pengembangan terhadap Kegiatan Bimbingan di Bina Keluarga Balita Kota Bandung) - Lilis Satriah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Parenting plays a very important role in building children’s character and personality, thus it requires the provision of good education and care (nurture) from parents in order to generate children with good character or moral.Parents, especially mothers, therefore, are demanded to possess good parenting skills. But the reality shows that most mothers in Bandung have poor parentingskillsa. It is shown by the large number of parents who still hold the authoritarian type of parenting, which amounts to 86.7%. This phenomenon ofpood parenting skills of mothers in the city of Bandung underlies the need for the arrangement of effective guidance model to improve the parenting skills of parents, especially mothers as the holder of an important role in the education of children in family. For if these parents are allowed to adopt the authoritarian type of parenting, then the character and personality of the children they bring up will be unfavorable, whereas moral or noble character is an important foundation in the establishment of a secure, serene, and peaceful society. Based on such phenomenon, the researcher tried to design a program of guidance supported with a group approach as an effort to enhance the parenting skills of mothers. The program is tested on mothers participating BKB (Bina Keluarga Balita) in Bandung. After going through a series of trials, the result obtained shows that a group guidance held in eight sessions, with the subject of: (1) Monitoring children's behavior, (2) Having effective communication with children, (3) Setting rules and limits, (4) Enforcing rules without collisions, (5) Stimulating the task of childen development, (6) Being a good listener, (7) Applying Love Languages, and (8) Complimenting children, proved to effectively improve the parenting skills of mothers. It is characterized by theshift of parenting type, from authoritarian to authoritative. In conclusion the counseling program with the group approach can be an alternative model of guidance that can be used to enhance the parenting skills of mothers in a variety of settings in the community; in Majlis taklim, it is one of the alternative methods of da’wa, in BKB (Bina Keluarga Balita) it is a model of community counseling, in early childhood education concerning the co-parenting program, it is an education model for parents.